Job Satisfaction And Organisational Citizenship Behaviour: An Empirical Study At Higher Learning Institutions - Mohammad, Jehad; Quoquab Habib, Farzana; Alias, Mohmad Adnan (Asian Academy of Management (AAM), 2011)
This study is designed to measure the two dimensions of organisational citizenship behaviour (i.e., OCBI and OCBO) and to examine how these organisational citizenship behaviours are related to the two facets of job satisfaction (intrinsic and extrinsic). To achieve the research objectives, the survey method is employed. Findings of this study reveal that both extrinsic and intrinsic job satisfaction are very important in predicting citizenship behaviour. Implications and limitations of the study are discussed along with suggestions for future research.